Spatial characterization of the tachycardia circuit of atrioventricular nodal re-entrant tachycardia. Issue 10 (8th July 2021) - Katritsis, Demosthenes G; Marine, Joseph E; Katritsis, George; Latchamsetty, Rakesh; Zografos, Theodoros; Zimetbaum, Peter; Buxton, Alfred E; Calkins, Hugh; Morady, Fred; Sánchez-Quintana, Damián; Anderson, Robert H
Abstract: Aims: The exact circuit of atrioventricular nodal re-entrant tachycardia (AVNRT) remains elusive. To assess the location and dimensions of the AVNRT circuit. Methods and results: Both typical and atypical AVNRT were induced at electrophysiology study of 14 patients. We calculated the activation time of the fast and slow pathways, and consequently, the length of the slow pathway, by assuming an average conduction velocity of 0.04 mm/ms in the nodal area. The distance between the compact atrioventricular node and the slow pathway ablating electrode was measured on three-dimensionally reconstructed fluoroscopic images obtained in diastole and systole. We also measured the length of the histologically discrete right inferior nodal extension in 31 human hearts. The length of the slow pathway was calculated to be 10.8 ± 1.3 mm (range 8.2–12.8 mm). The distance from the node to the ablating electrode was measured in five patients 17.0 ± 1.6 mm (range 14.9–19.2 mm) and was consistently longer than the estimated length of the slow pathway ( P  < 0.001). The length of the right nodal inferior extension in histologic specimens was 8.1 ± 2.3 mm (range 5.3–13.7 mm). There were no statistically significant differences between these values and the calculated slow pathway lengths. Conclusion: Successful ablation affects the tachycardia circuit without necessarily abolishing slow conduction, probably by interrupting the circuit at the septal isthmus. Graphical Abstract: